WADY WRODZONEMalignant mediastinal and left lung tumour – macroscopically radical resection in an infant with critical respiratory failure - Haponiuk, Ireneusz; Rzyman, Witold; Sroka, Mariusz; Drożyńska, Elżbieta; Chojnicki, Maciej; Murawski, Maciej; Hinc-Kasprzyk, Joanna; Skoczylas-Stoba, Barbara; Czauderna, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
We present a multidisciplinary surgical treatment of a male 4-month-old infant with malignant mediastinal and left lung tumour who deteri-orated rapidly with mechanical ventilation due to symptoms of local compression. The child underwent life-saving surgical intervention by a multidisciplinary team. Gross total resection of the tumour was achieved via a com-bination of median sternotomy and “hemi-clamshell” incision. After an uncomplicated postoperative period the child was transferred to the oncology department for further chemotherapy. Because of emergency hazardous resection the patient could be stabilized and subjected to continued chemotherapy, proving the possibility of multidisciplinary mediastinal tumour excision in emergency settings.